The imitation game: becoming imitators of Christ - Cockayne, Joshua (Religious studies, 2017)
What is it to lead a Christian life? At least part of the answer, from St Paul to Thomas à Kempis, to makers of WWJD bracelets, is to imitate Christ. But while there is a lot of practical advice in the spiritual literature for imitating Christ, there is little by way of philosophical analysis of what it is to imitate Christ. In this article, I aim to fill this lacuna. I argue that the imitation of Christ, as conceived of by St Paul, Thomas à Kempis, and others, requires a radical transformation of character, which, in turn, I argue, based on considerations from developmental psychology, requires direct engagement with Christ. This conclusion may be surprising, since Christ does not seem to be directly present to contemporary believers in the same way as, say, a mother is directly present to her infant child. I deal with this objection, and conclude with some applications of this approach to the philosophy of Christian spirituality.